Real-time big data analytics for hard disk drive predictive maintenance. (October 2018) - Su, Chuan-Jun; Huang, Shi-Feng
Abstract: Effective and reliable cloud services depend on the quality of service provided by large-scale data centers, and data center equipment reliability issues can cause significant data and financial loss to cloud service clients. Corrective maintenance is a reactive approach that only corrects problems once they occur, resulting in unwanted downtime, while preventative maintenance relies on replacing equipment which may yet still have considerable effective operating lifetime, thus raising maintenance costs. In contrast, predictive maintenance can potentially predict equipment failure in advance, thus reducing unplanned downtime and extending equipment lifetimes, thus reducing maintenance costs while increasing system reliability. This research aims to develop a real-time predictive maintenance system, HDPass, based on Apache Spark for the detection of imminent hard disk drive (HDD) failures in data centers.